Integrated Hydrodynamic and Electromechanical Modelling of Tidal Turbine PTO (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This work presents an advanced modelling and simulation framework for a tidal turbine coupled with a Permanent Magnet Synchronous Generator (PMSG). The proposed framework goes beyond conventional approaches by integrating a computational hydrodynamics model within a MATLAB/Simulink environment to simulate the turbine PTO. By replacing semi-empirical models traditionally used for the mechanical torque delivered by the rotor, a fast Boundary Integral Equation Method (BIEM) solver is used to predict the hydrodynamic response of the turbine, providing a more detailed and accurate representation of the mechanical loads generated by the rotor blades under variable onset flow and turbine RPM conditions. The BIEM-based computational methodology, developed at CNR-INM, is valid for horizontal-axis hydrokinetic turbines operating in arbitrary inviscid flow, and results have been extensively validated against Computational Fluid Dynamics (CFD) simulations and experimental data.In the proposed simulation framework, BIEM is integrated within a MATLAB/Simulink environment to dynamically compute the mechanical power and torque generated by the turbine blades in response to varying onset flow conditions. The BIEM output provides the input to the Simulink model, which includes detailed representations of the turbine drivetrain, the PMSG, the power converter, and the associated control systems. This holistic approach enables the evaluation of the turbine overall performance and the interaction between rotor hydrodynamics and the electrical subsystems.The proposed study highlights the advantages of incorporating BIEM over conventional models based on semi-empirical Cp-based relationships in scenarios involving non-uniform flow conditions. The proposed methodology ensures more accurate predictions of turbine hydrodynamic loads and power extraction capabilities, which is critical for optimizing the turbine operation, especially for MPPT control modelling.Numerical applications will be compared with results of the experimental characterization of a large-scale model turbine in the CNR-INM wave-towing tank. Key performance metrics, including power output and dynamic response in waves, will be evaluated to demonstrate the capability of the proposed methodology as a fast simulation tool to predict the turbine performance under varying operational conditions. The objective is to develop an enhanced simulation framework for performance assessments and informed decision-making in the development of next-generation tidal energy technologies.